2018
DOI: 10.3389/fpls.2018.01325
|View full text |Cite
|
Sign up to set email alerts
|

A Shoot Fe Signaling Pathway Requiring the OPT3 Transporter Controls GSNO Reductase and Ethylene in Arabidopsis thaliana Roots

Abstract: Ethylene, nitric oxide (NO) and glutathione (GSH) increase in Fe-deficient roots of Strategy I species where they participate in the up-regulation of Fe acquisition genes. However, S-nitrosoglutathione (GSNO), derived from NO and GSH, decreases in Fe-deficient roots. GSNO content is regulated by the GSNO-degrading enzyme S-nitrosoglutathione reductase (GSNOR). On the other hand, there are several results showing that the regulation of Fe acquisition genes does not solely depend on hormones and signaling molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(90 citation statements)
references
References 110 publications
4
86
0
Order By: Relevance
“…NO also preserves Fe homeostasis through crosstalk with ethylene and auxin phytohormones, ferritin and frataxin and through its ability to form nitrosyl iron complexes [162]. New elements, such as GSH, GSNO, and GSNO reductase, have been found in the complex relationships with the Long distance iron signal which moves from shoots to roots through the phloem to regulate Fe homeostasis [163]. GSNOR activity, in particular, has been found necessary for Fe homeostasis, especially under Fe-toxicity conditions in roots [164].…”
Section: Regulation Of Iron-responsive Element-iron Regulatory Proteimentioning
confidence: 99%
“…NO also preserves Fe homeostasis through crosstalk with ethylene and auxin phytohormones, ferritin and frataxin and through its ability to form nitrosyl iron complexes [162]. New elements, such as GSH, GSNO, and GSNO reductase, have been found in the complex relationships with the Long distance iron signal which moves from shoots to roots through the phloem to regulate Fe homeostasis [163]. GSNOR activity, in particular, has been found necessary for Fe homeostasis, especially under Fe-toxicity conditions in roots [164].…”
Section: Regulation Of Iron-responsive Element-iron Regulatory Proteimentioning
confidence: 99%
“…Recently, this model was supplemented by the regulatory role of GSNO and GSNOR in Fe-deficient roots. ET (ACC) was found to increase GSNOR activity and expression leading to low GSNO level which, through unblocking ET synthesis, can maintain ET production in Fe-deficient roots [159].…”
Section: No–et Interplay In Abiotic Stress Responsesmentioning
confidence: 99%
“…Under Fe starvation, a wide range of chemical signals coordinate and trigger the transcriptional response (Liu et al, 2016). Some studies have suggested that cellular Fe, especially the levels in leaf vasculature itself act as a sensing/signaling component (Kumar et al, 2017; Garcia et al, 2018; Khan et al, 2018). Based on these findings, together with action of R3 and R7, it is clear that multilayered signaling networks exist.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these findings, together with action of R3 and R7, it is clear that multilayered signaling networks exist. Importantly, there is lot of interconnection and feed-/forward-back between these signaling molecules, that influence each other, levels and activity under Fe-starvation (Garcia et al, 2011, 2018; Brumbarova et al, 2015; Liu et al, 2016). Therefore, further study of R3 may reveal the identity of a hidden unknown novel component that regulates the central transcription factor FIT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation